Injuries impacted a third of athletes who left the high-performance sport pathway. A 4-year retrospective study - Guevara, S.; Sheehy, D.; Waddington, G.; Drew, M.; Keegan, R.; Toohey, L. (Journal of Science and Medicine in Sport, 2024)
Introduction: Athlete health is considered a priority as it is known to affect successful performance in high-performance sport (HPS). Athlete health is also a top priority athlete retention issue to address. Nonetheless, one in four developing athletes entering a HPS academy program begin their elite sporting journey with an injury and were 2.5-times more likely to have a further in-season injury. There is a limited understanding of the relationship between physical health, in particular injuries, and its effect on positive (progression) or negative (attrition) pathway transition. This study aimed to investigate: (1) injury epidemiology, (2) how athletes transition through the HPS pathway; and 3) multiple reasons why athletes left HPS. Methods: A retrospective cohort study design was used in an Australian HPS state academy over a four-year period. Medical attention injuries were prospectively recorded. Injury incidence rates (IIR) and injury burden were calculated per 365 athlete-days, according to sex and pathway level. Athlete pathway levels were mapped to the Foundations, Talent, Elite and Mastery (FTEM) framework. Athletes` attrition reasons were reported. Results: Four hundred and eighty-one injuries were reported across 124 athletes at an IR of 2.09 injuries per 365 athlete-days (95%CI=1.91-2.29). Most athletes (103, 83%) were injured at least once over the four-year period. Injury burden across the cohort was 49.59 days absence per 365 athlete-days (95%CI=43.99-55.90). IIRs increased (IRR=1.17, 95%CI=1.06-1.29, p=0.001) as athletes progressed through the pathway. Thirty-six athletes left HPS, at FTEM levels T2-T4, of which 31% (n = 11) were impacted by injury. The most common reason for athlete attrition was deselection (n=18), with 56% of these athletes impacted by injury in the season prior to deselection. Discussion: This study found more than 80% of athletes sustained an injury over the surveillance period, IIR and burden were highest at elite FTEM levels, injury impacted a third of athletes who left HPS, and injury impacted over half of the deselected athletes. These results suggest that injury may negatively influence athletes progressing through the pathway and may indirectly through deselection, lead to subsequent attrition. These findings support the notion that injury is a key driver for pathway progression. As a result, earlier intervention and the development of preventative health initiatives would enable talented athletes to enter elite sport in a healthier and better prepared state to maximise their potential. Development of targeted prevention strategies to mitigate negative performance and attrition due to injury in developing athletes should be prioritised. Impact/Application to the field: This study highlights the importance of health surveillance in developing athlete academy programs, reporting on athlete progression and attrition throughout the pathway, and recording multiple reasons for why athletes may leave or get deselected out of HPS programs. This information can better inform governing level stakeholders on how best to support developing pathway athletes. By adjusting when and how health data is collected, and considering multiple contributing factors in analysis processes, the effectiveness of HPS pathway program health systems, can be refined to enhance developing athletes' performance and retention. Declaration: Two authors worked at an Australian or a state sporting institute at the commencement of this study. These institutes did not influence or approve the final version of this abstract.